Improving Mathematics and Science Education : a Longitudinal Investigation of the Relationship Between Reform-Oriented Instruction and Student Achievement. - Le, Vi-Nhuan (RAND Corp., 2006)
The term reform-oriented teaching describes a collection of instructional practices that are designed to engage students as active participants in their own learning and to enhance the development of complex cognitive skills and processes. This monograph presents the findings of a multiyear National Science Foundation (NSF)-funded study of the effectiveness of reform-oriented science and mathematics instruction. It builds on an earlier RAND study, called the Mosaic project, which found "a weak but positive relationship" between reform-oriented practices and student achievement. The present stu.